EFEKTIFITAS LAMA PASTEURISASI DAN PENYIMPANAN SUHU BEKU TERHADAP KUALITAS PASTA BAWANG MERAH (ALLIUM CEPA) - Bano, Isabela Gracela; Mushollaeni, Wahyu; Tantalu, Lorine (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to determine the effectiveness of pasteurization and storage on freezing temperatures to the quality of shallot paste with the feasibility analysis of the business of onion paste in dry form. In this study the stages of research implementation, best treatment analysis and business feasibility analysis were carried out. At the stage of the implementation of the study using several stages which include the stage of onion sorting, onion stripping, bleaching, paste making, citric acid mixing. While the best treatment analysis using the effectiveness index refers to (De Garmo 2004) with 3 steps namely Determination of Parameter Weight (BP ) and Normal Weight (BN), Determination of the worst and best value, determining the value of Effectiveness (NE) and Result Value (NH). For business feasibility analysis includes the calculation of BEP (Break Event Point), R / C (Revenue Cost Ratio) and HPP. The results obtained several factors that influence the quality of onion paste include: water content, pasteurization duration and storage time, total acid. The best treatment weight of each chemical analysis treatment performed resulted in the highest value found in C2 treatment, namely 35 seconds pasteurization and 12 days storage time with a value of 0.924. In terms of business feasibility, the planned product selling price of IDR 7,074.04 / pack of 100 grams. Net profit per day is IDR 92,270 / day and Based on the BEP calculation it is obtained to bring the BEP value of the price of IDR 30,630,600 / year. Tujuan penelitian ini mengetahui efektifitas lama pasteurisasi dan penyimpanan suhu beku pada kualitas pasta bawang merah beserta analisa kelayakan usaha pasta bawang merah dalam bentuk kering. Pada penelitian ini dilakukan tahapan pelaksanaan penelitian, analisa perlakuan terbaik dan analisa kelayakan usaha. Pada tahapan pelaksanaan penelitian menggunakan beberapa tahap yang meliputi tahap sortir bawang merah, pengupasan bawang merah, blancing, pembuatan pasta, pencampuran asam sitrat.Sedangkan analisa perlakuan terbaik menggunakan indeks efektifitas yang mengacu kepada (De Garmo 2004) dengan 3langkah yaitu Penentuan Bobot Parameter (BP) dan Bobot Normal (BN), Penentuan nilai terjelek dan terbaik, penentuan nilai Efektifitas (NE) dan Nilai Hasil (NH). Untuk analisa kelayakan usaha meliputi perhitungan BEP (Break Event Point),R/C (Revenue Cost Ratio) dan HPP.Hasil penelitian didapatkan beberapa faktor yang mempengaruhi kualitas pasta bawang merah antara lain : kadar air, Lama pasteurisasi dan lama penyimpanan, total asam.Bobot perlakuan terbaik dari setiap perlakuan analisa kimia yang di lakukan menghasilkan nilai tertinggi terdapat pada perlakuan C2 yaitu lama pasteurisasi 35 detik dan lama penyimpanan 12 hari dengan nilai 0,924. Dari sisi kelayakan usaha harga jual produk yang direncanakan pemasaran sebesar Rp. 7.074.04/kemasan 100 gram. Keuntungan bersih perhari sebesar Rp. 92,270/hari dan Berdasarkan peritungan BEP di peroleh bawa nilai BEP harga sebesar Rp. 30.630.600/tahun.